2010
DOI: 10.1139/b10-078
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny of two coelomycetous fungal genera with stellate conidia,ProsthemiumandAsterosporium, on Fagales trees

Abstract: Prosthemium (teleomorph Pleomassaria ) and Asterosporium (teleomorph unknown) are coelomycetous genera with stellate conidia on Fagales trees. Their morphological resemblance suggests their close relationship, but phylogenetic relatedness remains unknown. They have been distinguished on the basis of either conidiomatal morphology (pycnidia in Prosthemium and acervuli in Asterosporium) or their differing conidial septation (euseptate in Prosthemium and distoseptate in Asterosporium). To reveal their phylogeneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Morphological methods are described by Tanaka et al (2009, 2010). Monoconidial cultures were obtained according to the methods of Shearer et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…Morphological methods are described by Tanaka et al (2009, 2010). Monoconidial cultures were obtained according to the methods of Shearer et al (2004).…”
Section: Methodsmentioning
confidence: 99%
“…A more recent phylogenetic analysis included a group of coelomycete species with stellate conidia, isolated from Fagales trees clustered in Melanommataceae (Tanaka et al 2010; Plate 1). …”
Section: Notesmentioning
confidence: 99%
“…Mugambi and Huhndorf (2009a) suggested that the GenBank sequences of L. macrostomum (DQ384094) may be based on a misidentification. Taxa in ''Lophiostoma clade II'' sensu Zhang et al (2009b) are currently accepted as Lophiostoma sensu stricto by several authors (Mugambi and Huhndorf 2009a;Schoch et al 2009;Suetrong et al 2009;Tanaka et al 2010b). In the other genus, Lophiotrema, all species used in our study formed a highly supported monophyly with the exception of Lophiostoma vitigenum, and this clade was distantly placed from the Lophiostoma within the Pleosporales (Fig.…”
Section: Monophylies Of Lophiostoma and Lophiotremamentioning
confidence: 99%